Leptomastix dactylopii Howard (Hymenoptera: Encyrtidae): parasitoid of mealybugs (Hemiptera: Pseudococcidae) - Salman Al-Shami; Jawwad Qureshi (EDIS)
This publication describes the biology, distribution, behavior, and impact of the parasitoid Leptomastix dactylopii Howard. This beneficial insect is known for providing significant reductions in mealybug populations in Florida and other locations. It is also intended to provide knowledge about this parasitoid to a wide range of interested audiences including growers, Extension agents, researchers, students, laypersons, and other stakeholders.